White rot fungus TD95: Identification and pretreatment on wood chips for pitch control in the biopulping - Thi Hong Lien, Nguyen; Thi Huong, Tran; Van Hieu, Nguyen; Thi Hong Thao, Phan (VNU Journal of Science: Natural Sciences and Technology, 2017)
Wood extractives cause production troubles during pulp and paper manufacture, low-quality pulp, pitch deposition and effluent toxicity. New biotechnological solutions such as fungal pre-treatment of wood chips can reduce pitch problems. The fungus TĐ95, which showed high laccase and sterol esterase activity, was indentified and assessed for biodegradation of Acacia wood extractives. The fruiting bodies of strain TĐ95 were red brown, fan-shaped, thin with wrinkled margin. The hymenium was smooth. This fungus was firmly attached to the tree trunk. The colony was off-white, blossom, radiate. The internal transcribed spacer (ITS) region of rDNA gene sequence of TĐ95 was deposited onto GenBank (NCBI) under the accession number KY849400 . The fungus TĐ95 belongs to Perenniporia specie based on its morphological characteristic and an analysis of ITS – rDNA gene. This fungus TĐ95 could grow well on Acacia wood chips under solid state fermentation. After 15 days of incubation, total extract removal from wood was 47.31% by fungal degradation and holocellulose was not affected. The fungus TĐ95 could be used in pretreatment on wood chip for pitch control in the biopulping